APPLICATION OF MODERN PEDOGOGICAL TECHNOLOGIES IN TEACHING SPEAKING - Sevinchoy O’rinboyeva Qadam qizi (Ta’lim innovatsiyasi va integratsiyasi, 2023)
In today’s digital age ,educators are constantly seeking innovative ways to enhance the learning experience for their students.This is particularly true in the realm of language education , where traditional teaching methods are being supplemented and some cases, replaced by modern pedogogical technologies. Internet, podcasts ,videoconferencing ,videos and speech recognition software are considered the best tools for teaching speaking skill .This paper aims to discuss some new technologies available for teachers of English today to intensify speaking skill of second or foreign language learners